Religion and the Attentional Blink: Depth of Faith Predicts Depth of the Blink - Colzato, Lorenza S.; Hommel, Bernhard; Shapiro, Kimron (Frontiers in Psychology, 2010)
Religion is commonly defined as a set of rules, developed as part of a culture. Here we provide evidence that practice in following these rules systematically changes the way people allocate their attention, as indicated by the Attentional Blink (AB), a deficit in reporting the second of two target stimuli presented in close succession in a rapid sequence of distracters. We show that Dutch Calvinists and Atheists, brought up in the same country and culture and controlled for race, intelligence, mood, personality traits, and age, differ with respect to the amount of resources invested into processing AB targets. Calvinists showed a larger AB than Atheists, which is consistent with the notion that people's attentional processing style reflects biases rewarded by their religious beliefs.